الترادف بين كلمتي "اللعب واللهو" في القرآن الكريم (دراسة تحليلية دلالية) - Heriyadi; Lukman Syah, Burhan; Ulwan, Reza Aufa; Mohd Afandi, Aqila Najiha (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Synonyms in the qur'an have become a hotly discussed study. Arabic scholars debate the existence of synonyms or similarities of words found in the qur'an. One of the pairs of synonymous words that the author finds in the Qur'an is the words al-la'bu and al-lahwu which mean game and sindau joke. Of the two words, many people interpret that the two words are the same, but after going deeper, the two meanings have differences. Therefore, this research becomes very interesting and needs to be discussed. This study aims to: to find out the semantic meaning of the word Al-La'bu wa Al-Lahwu, the similarities and differences in the meanings of the two in the Qur'an. This research uses the library research method. The method used to collect data is the method of documentation relating to the sentences of Al-la'bu and Al-lahwu in the Qur'an. Data analysis using comparative methods. The results of this study are as follows: the word "al-la'bu" in its semantic aspect refers to the words al-istihzaa, al-a'bats, al-syuhkriyah, and al-hazlu. And the word "al-lahwu" from its semantic meaning refers to the words al-ilhaa, al-bathil, al-istihzaa, al-jauz aw al-walad, and al-toblu wa al-tasfikiq. the similarities and differences between the words Al-la'bu and Al-lahwu in the Qur'an in both have a semantic closeness, the two words share a meaning that is without actual wisdom and purpose. The difference between the two sentences is that the Al-la'bu sentence must be based on work and the Al-lahwu sentence based on a job or busyness of an important thing.